ETHNICITY AND ELECTORAL VIOLENCE IN AFRICA: AN ELITE THEORY PERSPECTIVE - Onuoha, Basil; Ufomba, Henry (PEOPLE: International Journal of Social Sciences, 2017)
The linkage between ethnicity, religious polarization and electoral violence in Africa has become one of the most recurring theme in the literature on democracy and elections in the continent. The electoral process in these emergent democracies have been observed to be marred by electoral violence which many have blamed on the diversity that characterize the socio-political configuration of these states which were inherited from European colonial powers at independence. In an attempt to explain the electoral violence phenomenon, existing works have limited the depths of their enquiry just below the surface by attributing the phenomenon to ethno-religious diversity which is prompted by competition for power and resource control. This paper makes an invitation for a deeper analysis by making a proposition based on the elite theory- which will serve as a framework for future studies on the subject matter. It proposes that the elite in Africa derive their support from their ethno-religious enclave and therefore have ethnic-based support structures. Since every society is shaped by the values and preferences of the elite, the demand of an ethno-religious enclave is therefore a reflection of the interest of the elite class in dominance of such enclave. As a result of this, ethnic competition and by extension electoral violence in African democratic experiments are a result of the clash of interest between these ethnic-based elite classes and their failure to harmonize their interest. To this end, we therefore suggest that electoral violence in Africa occurs mainly as ‘proxy wars’ between ethnic-based elite classes. Based on this assumption we propose that electoral violence is a function of the failure of the elite class from competing ethno-religious enclaves to harmonize their interest in an electoral process, and when harmonization of interest do occur there tends to be a peaceful election as was experienced in the 2015 presidential election in Nigeria which was peaceful despite the volatility of the political system at the time. This proposition sustains a new dimension in the debate and therefore provides itself as an analytical framework for future studies to build on.